2017
DOI: 10.1097/bpb.0000000000000374
|View full text |Cite
|
Sign up to set email alerts
|

Clinical application of back surface topography by means of structured light in the screening of idiopathic scoliosis

Abstract: We present the results of the clinical validity in the screening of idiopathic scoliosis with a nonharming method of back surface topography by means of structured light projection. A total of 155 patients were evaluated (mean age 13.3 years). They were divided into two groups: pathologic patients (scoliosis) and nonpathologic patients (control and asymmetries). An analytical case-control study was carried out. Our topographic method obtained 92% sensitivity and 74% specificity as a screening test in identifyi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 21 publications
0
21
0
Order By: Relevance
“…The use of RS in screening scoliosis is controversial [ 87 , 88 ]. Chowanska et al investigated if RS could replace the scoliometer in screening for scoliosis, using a portable rasterstereography device (CQ Electronic System, Wroclaw, Poland), and concluded that RS is not suitable for scoliosis screening.…”
Section: Surface Topography (Rasterstereography Rs)mentioning
confidence: 99%
See 1 more Smart Citation
“…The use of RS in screening scoliosis is controversial [ 87 , 88 ]. Chowanska et al investigated if RS could replace the scoliometer in screening for scoliosis, using a portable rasterstereography device (CQ Electronic System, Wroclaw, Poland), and concluded that RS is not suitable for scoliosis screening.…”
Section: Surface Topography (Rasterstereography Rs)mentioning
confidence: 99%
“…Also, the screening process took longer and the children had to uncover the entire back [ 87 ]. Conversely, using an experimental RS setup, Pino-Almero et al reported that RS has a higher specificity and sensitivity than the scoliometer in detecting scoliosis and recommended its use in the detection of scoliosis to reduce the use of radiography [ 88 ]. The difference in the interpretation of the results is possibly related to the fact that the former study considered the practical application of the screening while the latter study only considered the technical aspect of the findings.…”
Section: Surface Topography (Rasterstereography Rs)mentioning
confidence: 99%
“…The exclusion criterion was based on the SHS parameter. Although this parameter is well established in Surface Topography (ST) measurements [26,27,60,65,66,67,68], literature does not provide specific cut-off values for faulty posture. Thus, subjects with outlier values of the SHS distribution in any of the measurements were suspected of having a faulty posture and were excluded from the study.…”
Section: Methodsmentioning
confidence: 99%
“…The results are stored in a database so that the data of the particular patient can be recalled at any given point of time. ISIS2 helps in the screening and monitoring of the development of spinal deformity over time [71,72].…”
Section: The Integrated Shape Imaging System 1 and 2 (Isis1 And 2)mentioning
confidence: 99%
“…As seen in Figure 11, the ISIS2 system provides additional data to simple radiographic examination, describing the three-dimensional characteristics of the back surface [59,74]. Previous studies [71,72] have demonstrated that the ISIS2 produces reliable, valid and accurate data that can monitor the progression of spinal deformities. Berryman and Knott et al [33] suggest that the additional advantage of ISIS2 is to reduce the exposure to radiation.…”
Section: The Integrated Shape Imaging System 1 and 2 (Isis1 And 2)mentioning
confidence: 99%